Antibacterial Activity of a Chitosan-PVA-Ag+-Tobermorite Composite for Periodontal Repair. (7th April 2014) - Hurt, Andrew P.; Ruiz de Clavijo, Alejandra A.; Vine, George J.; Coleman, Aimee A.; Coleman, Nichola J.
Abstract : A polymer-mineral composite was prepared by solvent casting a mixture of chitosan, poly(vinyl alcohol), and Ag + -exchanged tobermorite in dilute acetic acid and characterised by scanning electron microscopy and Fourier transform infrared spectroscopy. The in vitro bioactivity of the CPTAg membrane was confirmed by the formation of hydroxyapatite on its surface in simulated body fluid. The alkaline dissolution products of the tobermorite lattice buffered the acidic breakdown products of the chitosan polymer and the presence of silver ions resulted in marked antimicrobial action against S. aureus, P. aeruginosa, and E. coli . The in vitro cytocompatibility of the CPTAg membrane was confirmed using MG63 osteosarcoma cells. The findings of this preliminary study have indicated that chitosan-poly(vinyl alcohol)-Ag + -tobermorite composites may be suitable materials for guided tissue regeneration applications.